Hugh T. Taggart collection relating to the District of Columbia and Maryland - Taggart, Hugh T. (Hugh Thomas), 1844-1914.; Beatty, Charles, of Georgetown, Md.; Canberry, Lewis; Cruikshank, Robert; King, Rt. (Robert), 1774 or 1775-1831.; Swan, Robert, active approximately 1828.; District of Columbia. Levy Court (Washington County); Georgetown (Washington, D.C.). Board of Commissioners; Falls Bridge Turnpike Company; Georgetown and Leesburg Turnpike Company
Correspondence, letterbooks, daybooks, minutes, notebooks, legal briefs, financial records, scrapbook, printed matter, broadside, and other papers and records collected by Taggart probably during his work on the Potomac Flats case determining waterfront boundary issues. Relates chiefly to the assessment, sale, and survey of property in the District of Columbia, Georgetown, and Maryland. Includes an account book of Charles Beatty; survey notebooks of Lewis Canberry; daybook and letterbook of Robert Cruikshank, a book dealer in Georgetown; survey notes of Rt. King; Robert Swan's sale catalog of books; daybooks of the Falls Bridge Turnpike Company and the Georgetown and Leesburg Turnpike Company; minutes of the Georgetown (Washington, D.C.) Board of Commissioners and the District of Columbia Levy Court (Washington County); assessments of personal property in Georgetown; surveys and sales of lots in the District of Columbia; and a book with manuscript mathematical exercises and colored drawings. Subjects include Daniel Carroll of Duddington, Pierre Charles L'Enfant, the colonial history of Maryland, and the Washington Canal, Washington, D.C.
appropriate custodial divisions of the Library of Congress.
U.S. district attorney.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carroll, Daniel, -- 1764-1849.; L'Enfant, Pierre Charles, -- 1754-1825.; Canals -- Washington (D.C.); Mathematics -- Problems, exercises, etc; Real property -- Maryland; Real property -- Washington (D.C.); Roads -- Virginia; Roads -- Washington (D.C.); Waterfronts -- Washington (D.C.); Georgetown (Washington, D.C.) -- History; Georgetown (Washington, D.C.) -- Surveys; Maryland -- History; Maryland -- History -- Colonial period, ca. 1600-1775.; Maryland -- Surveys; Washington Canal (Washington, D.C.); Washington (D.C.) -- History; Washington (D.C.) -- Surveys; Lawyers